Synthesis of 3-[3-(Benzothiazol-2-yl)-4-oxo-thiazolidin-2-yl]chromones as Antifungal Agents - Prabha Sharma, Vinay; Kumar, Praveen; Sharma, Meenakshi (Asian Journal of Chemistry, 2011)
Antifungal activities associated with chromones and thiazolidones prompted us to synthesize 3- [3-(benzothiazol-2-yl)-4-oxo-thiazolidin-2-yl]chromones through the intermediacy of Schiff bases. Structures of new compounds have been assigned by the interpretation of their IR and PMR spectral data and are supported by elemental analysis. One of the Schiff base adduct has shown high antifungal activity (90.93 % inhibition of growth) against Aspergillus niger i.e., the fungus responsible for food poisoning and aspergillosis. It is worth mentioning as the isolation and purification of Schiff bases was not easy due to 1,4-adduct formation. Hence, a one pot synthesis of title compounds was designed by refluxing a mixture of 3-formylchromone, 2-aminobenzothiazole and thioglycollic acid (TGA) in benzene in presence of zinc chloride instead of reacting Schiff base with thioglycollic acid.